ANALISIS EFEKTIVITAS KOMUNIKASI PELAYANAN PUBLIK PADA DESAIN ANTARMUKA PENDAFTARAN AKUN PADA WEBSITE oss.go.id - Pohan, Syafruddin; Simamora, Andreas Julangdi Java (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
Nowadays, public service is no longer limited by time and space, which means anything could happen whenever and wherever. People could access a certain website and receive public service to accommodate their needs through that website. One of the criteria of good public service is how the acceptance level of public service in the public which are formed by various background, either by one with good education in IT or the ordinary one. The OSS website offers easiness for people to receive public service from the government independently. This research will try to dissect about is the interface of OSS website really capable to accommodate the needs of the people.